Early Life Interventions Can Shape Aging - Bartke, Andrzej; Sun, Liou Y.; Li, Xinna; Miller, Richard A. (Frontiers in Endocrinology, 2022)
It is well documented that the environment of the developing fetus, including availability of nutrients and presence of toxins, can have major impact on adult phenotype, including age-related traits and risk of chronic disease. There is also accumulating evidence that postnatal environment can impact adult characteristics related to evolutionary fitness, health, and aging. To determine whether early life hormonal interventions can alter trajectory of aging, we have examined the effects of early life growth hormone (GH) replacement therapy in Prop1df (Ames dwarf) mice which are GH deficient and remarkably long lived. Twice-daily GH injections between the ages of two and eight weeks completely normalized ("rescued”) a number of adult metabolic characteristics believed to contribute to extended longevity of these mutants. Importantly, longevity of Ames dwarf mice was reduced by early life GH treatment. This was associated with histone H3 modifications. Apparently, the trajectory of mammalian aging can be modified by early life interventions. Mechanistic links among interventions during postnatal development, adult metabolic characteristics, aging, and longevity, apparently involve epigenetic phenomena.po